2006
DOI: 10.4049/jimmunol.176.3.1908
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Situ Expression of IL-23 by Keratinocytes in Healthy Skin and Psoriasis Lesions: Enhanced Expression in Psoriatic Skin

Abstract: Keratinocytes contribute to cutaneous immune responses through the expression of cytokines. We investigated whether human keratinocytes can express IL-23, a newly defined IFN-γ-inducing cytokine composed of a unique p19 subunit and a p40 subunit shared with IL-12. Cultured keratinocytes from normal and lesional psoriatic skin were found to express constitutively mRNA for both subunits of IL-23. Low but significant levels of the heterodimeric IL-23 protein could be detected in cell lysates and supernatants from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
264
1
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 409 publications
(297 citation statements)
references
References 41 publications
15
264
1
8
Order By: Relevance
“…[49][50][51][52] Moreover, psoriatic skin lesions also contain high mRNA and protein levels of IL-23 compared with non-lesional and normal skin and IL-23 has been found to be produced mainly by the activated macrophages and DCs. [53][54][55] Intradermal injection of IL-23 or IL-21 in mice can stimulate keratinocytes proliferation and cause epidermal hyperplasia (acanthosis), which is one of the most significant features in human psoriasis. 51,56 Further studies demonstrated that IL-22, IL-17A as well as CC chemokine receptor (CCR) 6 are all required for IL-23-induced psoriasis-like skin inflammation.…”
Section: Is Psoriasis a Th1 And/or Th17 Cell-mediated Inflammatory Skmentioning
confidence: 99%
“…[49][50][51][52] Moreover, psoriatic skin lesions also contain high mRNA and protein levels of IL-23 compared with non-lesional and normal skin and IL-23 has been found to be produced mainly by the activated macrophages and DCs. [53][54][55] Intradermal injection of IL-23 or IL-21 in mice can stimulate keratinocytes proliferation and cause epidermal hyperplasia (acanthosis), which is one of the most significant features in human psoriasis. 51,56 Further studies demonstrated that IL-22, IL-17A as well as CC chemokine receptor (CCR) 6 are all required for IL-23-induced psoriasis-like skin inflammation.…”
Section: Is Psoriasis a Th1 And/or Th17 Cell-mediated Inflammatory Skmentioning
confidence: 99%
“…We did not observe a reduction in IL-23p19 mRNA expression in epidermal and whole PP skin after IL-4 stimulation. However, this corresponds with a previous study stating that psoriatic KC lack intrinsic aberrant expression of IL-23, and therefore, IL-23 may not be further reduced by IL-4 in culture conditions (52). In addition, IL-1b and IL-6 are necessary for Th17 induction by DC (6,10).…”
Section: Discussionmentioning
confidence: 42%
“…IL-23p19 is increased in PP and can be produced by KC, but DC are the main source (40,51,52). Reports showed that IL-23 production by DC is inhibited by IL-4 and that downmodulation of DC and IL-23p19 is an early effect during psoriasis treatment (20,26).…”
Section: Discussionmentioning
confidence: 99%
“…IL-23, then, subsequently may provide a stimulus for the proliferation of the Th17 cells [22,23]. Dendritic cells secrete IL-23-along with IL-12, another key cytokine for Th1 differentiation-but IL-23 also can be produced by keratinocytes and non-dendritic, antigenpresenting cells [24][25][26]. IL-23, a heterodimeric cytokine in the IL-12 family, is composed of the p19 and p40 subunits that can then bind to the receptor made up of IL-12Rβ1 and IL-23R [27].…”
Section: Background: the Interleukin (Il)-23/t Helper (Th)17 Pathwaymentioning
confidence: 99%